2004
DOI: 10.1016/j.str.2004.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Pathway Complexity of Alzheimer's β-Amyloid Aβ16-22 Peptide Assembly

Abstract: Recent studies suggest that both soluble oligomers and insoluble fibrils have toxic effects in cell cultures, raising the interest in determining the first steps of the assembly process. We have determined the aggregation mechanisms of Abeta(16-22) dimer using the activation-relaxation technique and an approximate free energy model. Consistent with the NMR solid-state analysis, the dimer is predicted to prefer an antiparallel beta sheet structure with the expected registry of intermolecular hydrogen bonds. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
222
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(243 citation statements)
references
References 49 publications
20
222
1
Order By: Relevance
“…Using the ART and an approximate free energy model, Santini et al showed that an in-register antiparallel -sheet structure was the most stable structure for the A (16)(17)(18)(19)(20)(21)(22) dimer, despite the existence of several hydrogen bond patterns in both parallel and antiparallel orientations that were thermodynamically possible [110,111]. The existence of alternative -sheet organizations is important because it helps explain the dependence of -sheet registry on pH [105] and amino acid composition [112].…”
Section: A Assembly Of a (16-22)mentioning
confidence: 99%
“…Using the ART and an approximate free energy model, Santini et al showed that an in-register antiparallel -sheet structure was the most stable structure for the A (16)(17)(18)(19)(20)(21)(22) dimer, despite the existence of several hydrogen bond patterns in both parallel and antiparallel orientations that were thermodynamically possible [110,111]. The existence of alternative -sheet organizations is important because it helps explain the dependence of -sheet registry on pH [105] and amino acid composition [112].…”
Section: A Assembly Of a (16-22)mentioning
confidence: 99%
“…14,15 In its current implementation (ART nouveau), 15 the method was also adapted to systems having high and low-frequency vibrational modes 17 and was used to study the folding pathways of a ␤-hairpin peptide model as well as multimers of amyloid-forming peptides. 18,31,32 In all cases, ART in Cartesian coordinate space succeeded in identifying folding mechanisms considerably more complex than those previously proposed. As an example, ART combined with a simplified generic force field (OPEP [33][34] ) revealed that the rate-limiting in the assembly of three peptide chains into a cross-␤ structure involves the reptation of one strand over another.…”
Section: Artmentioning
confidence: 81%
“…This is an important problem because there is both experimental and theoretical evidence that multidomain proteins are not rigidly packed, but are rather dynamic structures. 42,43 For these initial tests, we use a helical-hairpin model derived from the PDB entry 1ABZ 44 and consisting of two ␣-helices (residues 6 -16 and 22-33) connected by a loop (residues [17][18][19][20][21]. This system contains 399 atoms and has 242 internal coordinates.…”
Section: Two-domain Protein Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation of two short Aβ (16)(17)(18)(19)(20)(21)(22) peptides by Santini et al 18 showed multiple complex routes to fibrillization involving various networks of hydrogen bonds.…”
Section: Hydrogen Bonds and Aggregationmentioning
confidence: 99%